Lipid profiles of blood serum and fatty acid composition of meat of hybrid duck fed diet supplemented with Noni (Morinda citrifolia) fruit meal - Kurniawan, David; Widodo, E.; Djunaidi, I. H. (Indonesian Animal Sciences Society, 2015)
Noni fruit is a medicinal plant with biological activity like antioxidant that could potentially be used as a feed additive in poultry. This research investigated the effect of noni fruit powder as feed additive on lipid profiles of blood and meat fatty acid compositions of meat of hybrid duck. One hundred twenty 2-week-old hybrid ducks crossing between Peking and Khaki Campbell duck were subjected. They were randomly allotted to 24 experimental units. Each experimental unit was 70x80x40 cm in size and it was used for 5 ducks up to they reached 56 days of age. Each unit was equipped with waterer and feeder. The ducks were raised on litter-type floor. The basal experimental diet was formulated according to the standards of National Research Council (1994). The method used for this study was experimental with 4 different treatments in 6 replications. The treatments were as follow: P0: basal feed without supplementation of noni fruit powder as control; P1: basal feed + 1 % noni fruit powder; P2: basal feed + 2 % noni fruit powder; P3: basal feed + 3 % noni fruit powder. Data were analyzed by one-way of Completely Randomized Design ANOVA and if there was significant effect followed by Duncanâs Multiple Range Test. Result showed that using noni fruit powder as feed additive had no significant effect (P>0.05) on lipid profiles of blood and fatty acid composition of meat. Key Words: Noni Fruit, Phytobiotic, Fatty Acid, Blood Lipid